КУЛЬТУРА МОВЛЕННЯ ЯК ЕЛЕМЕНТ ДУХОВНОЇ КУЛЬТУРИ СУСПІЛЬСТВА - Царик, Ольга (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті окреслено перспективи вивчення культури мовлення як елементу духовної культури суспільства із врахуванням сучасних підходів до аналізу основних філософсько-соціологічних понять. Для дослідження використано герменевтичну інтерпретацію. Проаналізовано культуру та мистецтво спілкування як засіб духовного розвитку та вдосконалення особистості та суспільства. На прикладі діяльності українського вченого Івана Огієнка розглянуто методичні особливості процесу формування культури мовлення, розвитку та утвердження української мови у сфері освіти початку ХХ століття. В статье обозначены перспективы изучения культуры речи как элемента духовной культуры общества с учетом современных подходов к анализу основных философско-социологических понятий. Для исследования использована герменевтическая интерпретация. Проанализирована культура и искусство общения как средство духовного развития и совершенствования личности и общества. На примере украинского ученого Ивана Огиенко рассмотрены методические особенности процесса формирования культуры речи, развития и утверждения украинского языка в сфере образования начала ХХ века. The article outlines the prospects for the study of speech as part of the spiritual culture of society, taking into account modern approaches to the analysis of the major philosophical and sociological concepts. Hermeneutic interpretation was used for the study. It was found that culture as a social process and function is realized and develops in human activities, language as an important means of direct or indirect organization of this process is an important element of national forms of culture. It is noted that the culture of language shows the development of the individual intellect and high general culture of society. High linguistic culture can be achieved with the development of thinking. Language in which excellence of informative and communicative functions are provided by ratio of oral and written, spoken and literary language, indicates a high level of spiritual culture of society. The culture and art of communication were analyzed as a means of spiritual development and improvement of the individual and society. In the example of the Ukrainian scientist Ivan Ohiyenko methodological features of the process of speech formation, development and consolidation of the Ukrainian language in education early twentieth century were considered.